Family violence in African communities in the Western Cape : s theological-ethical assessment - Rashe, Reuben Zolile (Stellenbosch : Stellenbosch University, 2008)
Thesis (DTh (Systematic Theology and Ecclesiology)--Stellenbosch University, 2008.